ON THE CONCEPT OF BOOK MONUMENTS: SOME THEORETICAL AND PRACTICAL ASPECTS - BRAZIŪNIENĖ, ALMA (Knygotyra, 2011)
The article, based on various Lithuanian and foreign publications as well as on the author’s empirical material, deals with the concept of book monuments in the today’s situation in Lithuania. The author examines whether the current talks about the Lithuanian book monuments is actual, what we are winning or losing from the legally validated book monuments, what is being done in the field of book monuments in Lithuania. To UNESCO activities at issue in the documentary heritage identification and protection are analysed. The conclusion is done that in this networking century when the preeminence of cultural heritage rather than monumentalism is declared, one cannot avoid an active discourse on book monuments. The research of book monuments remains relevant.
Keywords: ...